Effectiveness of Eco Farming as Organic Fertilizer on Vegetative Growth Basil (Ocimum Basilicum L.) - Anggraini, Dwi; Idris, M; Rahmadina, Rahmadina (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The Indonesian people are familiar with the herbaceous vegetable plant known as basil (Ocimum basilicum L.). The leaves of the basil plant are typically used to flavor cuisine and as fresh vegetables. This study set out to determine how applying liquid organic fertilizer from eco farming affected basil plants' ability to grow vegetatively (Ocimum basilicum L.) as well as the optimal dosage for this growth. August and September of 2023 saw the completion of this study. Using three treatments and five replications, the research employed a Randomized Block Design (RAK) methodology. Treatment A0 was the control, receiving no fertilizer; treatment A1 received 4 milliliters of eco-farm fertilizer; and treatment A2 received 6 milliliters of eco-farm fertilizer. The characteristics that need to be taken into account include plant height, number of branches, leaf area index, number of leaves, initial and final soil analysis, and chlorophyll content. The study data will be analyzed using statistical products and services solutions (SPSS) software version 25. The administration of 6 milliliters of eco-farm fertilizer to plants, or treatment A2, had a significant effect on the vegetative development of Ocinum basilicum L. basil plants, according to the research findings. Measurements of plant height are affected by a concentration of 6 ml. The highest average value for number of leaves is 30.00, while the highest average value for height is 39.60, the highest average value of 3.35 for leaf area index, and the highest average for leaf area index. 4.0 for number of branches.